2017
DOI: 10.12669/pjms.333.12166
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexual dysfunction in Saudi women with Type 2 diabetes: Is it affected by age, glycemic control or obesity?

Abstract: Objective:Sexual dysfunction (SD), as a diabetes mellitus (DM)-related complication, is common among patients having diabetes. This study aimed to ascertain the prevalence of SD in Saudi women with type 2 DM and to determine whether age, glycemic control, and obesity are associated with SD or not.Methods:A total of 275 Saudi women with type 2 diabetes took part in this cross-sectional study and filled out the Female Sexual Function Index through a fill-coded questionnaire in primary care clinics in King Khalid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
3
12
0
2
Order By: Relevance
“…In the present study, FSD has been reported to be more prevalent among participants who have lower levels of education. This result is similar to other study results, [22,45,47] but contrarily to other studies results. [43,48] With regard to having a job, non-job status was significantly high among sexual dysfunction women while professional work was high among women without sexual dysfunction.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, FSD has been reported to be more prevalent among participants who have lower levels of education. This result is similar to other study results, [22,45,47] but contrarily to other studies results. [43,48] With regard to having a job, non-job status was significantly high among sexual dysfunction women while professional work was high among women without sexual dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…As for body mass index (BMI), no statistically significant difference was found between the two groups regarding their body mass index whereas the most women of both groups were overweight and obese. This result is accordance with previous other studies results [37,46,47,50] while it is a contrast to other. [51] The differences in the menstrual, obstetric parameters and number of living children among female without sexual dysfunction and dysfunctional sexual women were statistically insignificant.…”
Section: Discussionsupporting
confidence: 93%
“…8,33 Furthermore, female sexual dysfunction is observed in women with other risk factors such as diabetes, cardiovascular disease, hypertension, metabolic syndrome and polycystic ovary syndrome. 26,34 Considering diabetes mellitus as a risk factor for sexual dysfunction, AlMogbel et al 35 investigated the prevalence of sexual dysfunction in women with type 2 diabetes mellitus to determine whether age, glycemic control and obesity are associated with female sexual dysfunction. In this study, obesity was linked with a slight increase in sexual dysfunction; the prevalence of dysfunction among women with type 2 diabetes was high (88.7%) and increased with age (92% in the over 50-year-old age group).…”
Section: Risk Factorsmentioning
confidence: 99%
“…In this study, obesity was linked with a slight increase in sexual dysfunction; the prevalence of dysfunction among women with type 2 diabetes was high (88.7%) and increased with age (92% in the over 50-year-old age group). 35 However, hyperglycemia was the main determinant of vascular diabetic complications and participated in pathogenic mechanisms of sexual dysfunction in diabetics. 35 Cardiovascular disease shares several risk factors with sexual dysfunction, and there is evidence of common pathophysiologies such as atherosclerosis, endothelial dysfunction and subclinical inflammation.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation